Measurement of strange baryon production in charged-particle jets in pp and p-Pb collisions with ALICE - van Weelden Gijs (EPJ Web of Conferences)
The enhancement of the ratio of strange to non-strange hadrons with increasing charged-particle multiplicity density is often interpreted as a signature of the medium formed in heavy-ion collisions. However, this effect has also been observed in smaller systems, such as pp and p–Pb collisions. Understanding this effect requires a detailed description of the production mechanisms of strange hadrons in and out of jets. In this manuscript published results on the production of KS0, Λ(Λ¯), Ξ± and Ω± hadrons in charged-particle jets and the underlying event in pp and p-Pb collisions measured by ALICE are presented. In addition, a new analysis of in-jet fragmentation into Λ and KS0 hadrons in pp collisions at √s = 13.6 TeV from LHC Run 3 data is shown.